Proton Transport Studies in Dehydrated Salts: AlNH4(SO4)2 and FeSO4 - Pandey, Kamlesh; Mauli Dwivedi, Mrigank (Asian Journal of Chemistry, 2016)
Dehydrated aluminium ammonium sulphate and ferrous sulphate have shown good protonic behaviour (H+ ion movement) after the insertion of external hydrogen in the intermediate temperature range (200–4000°C) as studied by polarization experiment, IR spectroscopy, electrochemical e.m.f measurement and electrical conductivity measurement in air and hydrogen ambient.